Family environment and early sexual behaviour among adolescents: a cross-national study in 10 countries - Lenčiauskienė, Ilona; Zaborskis, Apolinaras (2007)
Background Early sexual initiation is an important issue that can result in adverse health, social and economic consequences for adolescents and their families. The family is one of the earliest and most important influences on adolescent sexual development and plays an important role in sexual risk-taking among teens. According to the current multivariate findings the factors, such as family connectedness, parent–child communication, parenting style and family structure have been identified as determinants to early sexual behaviour. The aim of this study was to identify the influence of family structure, parent-teen relationship and parental control on adolescents’ involvement in early sex. Methods The study was undertaken in the context of the WHO collaborative HBSC study. The representative samples were drawn in nine European countries and Israel. The group of 14287 (6716 boys and 7571 girls) 15-year-olds was surveyed. The data were collected by standardized questionnaires. Adolescents were asked about sexual behaviour, family structure, parent–teen communication, parental control. The quantitative analyses including frequency distributions, chi-square tests and multilevel logistic regression analysis were applied to assess the influence of determinants on adolescents’ early sexual behaviour. Results Even 33.5% of boys and 28% (P < 0.05) of girls reported to have had sexual intercourse before the age of 16 in nine European countries. Greenlandic teens were predominantly engaged in early sex. Intact family significantly decreases the possibility to be engaged in early sexual behaviour both [.].